2017
DOI: 10.4172/2155-9899.1000489
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Nrf2 and NF-κB in Neuroinflammatory Diseases

Abstract: Many neurodegenerative conditions involve redox imbalance and neuroinflammation. Nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor-κB (NF-κB) are key transcription factors regulating antioxidant and inflammatory pathways, respectively. These two opposing factors are inversely regulated, with activity of one most often accompanied by diminished activity of the other, giving rise to the oxidative stress and neuroinflammation evident in neurodegeneration. Emerging evidence is uncovering a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…As shown in the current study, NF‐κB is assumed to be regulated by oxidative stress after treatment with tamoxifen, that controlled by Nrf2 after exposure to radiation and sildenafil. This was in accordance with 31 who reported that, activation of NF‐κB signaling by oxidative stress and inhibition of NF‐κB signaling in the occurrence of antioxidants. This led to speculations that Nrf2 may NF‐κB activity by eliminating oxidative stress and through activation of several antioxidant enzymes such as quinone oxidoreductase, Paraoxonase, catalase, reduced glutathione and superoxide dismutase 29,32–34 .…”
Section: Discussionsupporting
confidence: 93%
“…As shown in the current study, NF‐κB is assumed to be regulated by oxidative stress after treatment with tamoxifen, that controlled by Nrf2 after exposure to radiation and sildenafil. This was in accordance with 31 who reported that, activation of NF‐κB signaling by oxidative stress and inhibition of NF‐κB signaling in the occurrence of antioxidants. This led to speculations that Nrf2 may NF‐κB activity by eliminating oxidative stress and through activation of several antioxidant enzymes such as quinone oxidoreductase, Paraoxonase, catalase, reduced glutathione and superoxide dismutase 29,32–34 .…”
Section: Discussionsupporting
confidence: 93%
“…It is believed on the basis of various studies that NRf2 by increasing anti-oxidant activity can mitigate NFκB activity and hence play a neuroprotective role. Redox status of the cells regulate the expression of NFκB, which in turn is regulated by Nrf2 (Liddell 2017 ).…”
Section: Various Pathways Playing Role In Neuroinflammationmentioning
confidence: 99%
“…However, under conditions of oxidative stress, Nrf2 dissociates from Keap1 and translocates and accumulates in the nucleus where it binds to antioxidant response elements, promoting the transcription of hundreds of genes (Liddell, 2017).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%